Comunicação humana e seus distúrbios: formação e capacitação de professores de Educação Física - Brandão, Mariane da Silva (2014)
The present study aimed to analyse the formation and the training of physical education teachers regarding the identification, referral and performance with students who exhibit disorders of human communication. The study is quantitative character, is characterised as transversal and its methodological option to exploratory-descriptive research but also the analytical character. In the first stage of the study to analyze the initial training of teachers, 426 were analyzed curricula (curricular or curricular grids arrays) online physical education courses-Degree of public and private universities throughout Brazil, referring to identify whether the theme of human communication Disorders is covered or not. . It can be concluded at this stage that 99% of the courses studied, not address the topic in his starting line-up. In the second stage of the research, to analyze the training of teachers, were contacted to participate in the entire study population of physical education teachers in the city of Santa Maria-RS (88 teachers), for which he was sent the link to the data collection instrument and, of these, 62 were respondents, which was constituted in the sample of this research. The data were collected with the Google Docs Offline tool ®, with autoaplicado questionnaire. For data analysis we used descriptive statistics of the variables studied, using frequency distribution, and the results, grouped into tables. At the end of this step, it is concluded that the majority of teachers, from its initial formation, do not consider themselves empowered to identify, escalate and work with students with disorders of human communication. Given this context, it is possible to point out the need for a reorganization of the curriculum of the course in question, so that we can reflect on what do teacher. It is evident the need for physical education teachers have knowledge on the subject of study, in order to intervene and minimize their effects, in search of help in the development of the communication of its students in its prevention and treatment, and to provide a better quality of life and teaching-learning students under its guidance.